Blood–Brain Barrier Dysfunction as a Hallmark Pathology in Chronic Traumatic Encephalopathy. Issue 7 (July 2016) - Doherty, Colin P.; O'Keefe, Eoin; Wallace, Eugene; Loftus, Teresa; Keaney, James; Kealy, John; Humphries, Marian M.; Molloy, Michael G.; Meaney, James F.; Farrell, Michael; Campbell, Matthew
Abstract : Chronic traumatic encephalopathy (CTE) is a neurodegenerative condition associated with repetitive mild traumatic brain injury. In recent years, attention has focused on emerging evidence linking the development of CTE to concussive injuries in athletes and military personnel; however, the underlying molecular pathobiology of CTE remains unclear. Here, we provide evidence that the blood–brain barrier (BBB) is disrupted in regions of dense perivascular p-Tau accumulation in a case of CTE. Immunoreactivity patterns of the BBB-associated tight junction components claudin-5 and zonula occludens-1 were markedly discontinuous or absent in regions of perivascular p-Tau deposition; there was also immunohistochemical evidence of a BBB in these foci. Because the patient was diagnosed premortem clinically as having progressive supranuclear palsy (PSP), we also compromised that the CTE alterations appear to be distinct from those in the brain of a patient with PSP. This report represents the first description of BBB dysfunction in a pathologically proven CTE case and suggests a vascular component in the postconcussion cascade of events that may ultimately lead to development of a progressive degenerative disorder. BBB dysfunction may represent a correlate of neural dysfunction in live subjects suspected of being at risk for development of CTE.